2022
DOI: 10.21468/scipostphys.12.1.018
|View full text |Cite
|
Sign up to set email alerts
|

Relating the topology of Dirac Hamiltonians to quantum geometry: When the quantum metric dictates Chern numbers and winding numbers

Abstract: Quantum geometry has emerged as a central and ubiquitous concept in quantum sciences, with direct consequences on quantum metrology and many-body quantum physics. In this context, two fundamental geometric quantities are known to play complementary roles:~the Fubini-Study metric, which introduces a notion of distance between quantum states defined over a parameter space, and the Berry curvature associated with Berry-phase effects and topological band structures. In fact, recent studies have revealed direct rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 88 publications
0
17
0
1
Order By: Relevance
“…The above three-parameter model enables us to study both quasi-classical (γ = 0) and coherent (γ = 1) cases. That model, as well as the two-level model |ψ(θ, φ) = cos θ 2 |0 − sin θ 2 e −iφ |1 , is indeed one of the eigenstates of a gapless Weyl-type Hamiltonian that hosts monopoles at the origin of parameter space [27,29], leading to γ = 1 (or 0 at special points). To study intermediate cases where γ ≤ 1, one can consider different geometrical models [32] or, as done here, rely on the two-parameter subspaces of the above three-parameter model where γ is a function of α.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The above three-parameter model enables us to study both quasi-classical (γ = 0) and coherent (γ = 1) cases. That model, as well as the two-level model |ψ(θ, φ) = cos θ 2 |0 − sin θ 2 e −iφ |1 , is indeed one of the eigenstates of a gapless Weyl-type Hamiltonian that hosts monopoles at the origin of parameter space [27,29], leading to γ = 1 (or 0 at special points). To study intermediate cases where γ ≤ 1, one can consider different geometrical models [32] or, as done here, rely on the two-parameter subspaces of the above three-parameter model where γ is a function of α.…”
mentioning
confidence: 93%
“…That model, as well as the two-level model |ψ(θ, φ) = cos θ 2 |0 − sin θ 2 e −iφ |1 , is indeed one of the eigenstates of a gapless Weyl-type Hamiltonian that hosts monopoles at the origin of parameter space [27,29], leading to γ = 1 (or 0 at special points). To study intermediate cases where γ ≤ 1, one can consider different geometrical models [32] or, as done here, rely on the two-parameter subspaces of the above three-parameter model where γ is a function of α. From the viewpoint of the Hamiltonian, this corresponds to taking a slice of the original gapless Weyl-type system, which yields a gapped topological insulator that can have γ ≤ 1.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…A prominent tool to analyze ME is the quantum Fisher information (QFI) [57][58][59], which is also also central in quantum metrology [60,61]. The QFI has been investigated in topological [33,[62][63][64][65][66] as well as spin [67][68][69][70][71][72] and lattice [73,74] systems, and used to characterize interesting many-body phenomena such as quantum criticality [75][76][77], quantum chaos [78,79], quantum quenches [80,81], scrambling [82] and thermalization [83,84].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the imaginary part of this tensor corresponds to the Berry curvature, which plays a central role in quantum Halltype transport [39,40] and topological defects [41]. Surprisingly, inspired by the existence of correlations between the quantum metric and the Berry curvature, it has been recently suggested that the Berry curvature (and the related Chern numbers) can set bounds on quantum multi-parameter estima-tion [42,43]. Demonstrating the connection between topology and quantum metrology in experiments is highly appealing, however, accessing the limits of quantum multi-parameter estimation is a challenging task and an experimental verification has remained elusive.…”
mentioning
confidence: 99%